PENGARUH PARTISIPASI MASYARAKAT, KOMPETENSI PENDAMPING DESA, KOMPETENSI APARATUR DESA, KUALITAS PENGAWASAN BADAN PERMUSYAWARATAN DESA SERTA KOMITMEN PEMERINTAHAN DAERAH TERHADAP KEBERHASILAN PENGELOLAAN DANA DESA - Dilla, Anisyah Martha; Coryanata, Isma (ITB AAS Indonesia Surakarta, 2024)
This study aims to test and prove the influence of community participation variables, the competence of village assistants, the competence of village officials, the quality of supervision of village consultative bodies and the commitment of local governments to the successful management of village funds in Kaur Tengah District, Kaur Regency. This research uses quantitative methods. The sampling technique used is non probability sampling (saturated sampling) and the type of data in this study is primary data. The sample in this study were all village governments (Village Head (Kades), Village Secretary (Sekdes), Village Treasurer, Head of Affairs (Kaur), Section Head (Kasi)) as many as 96 people. The data collection technique used in this study was through distributing questionnaires to respondents. Technical analysis and hypothesis testing using Partial Least Square (PLS) tools using SmartPLS 4.0 application software. The results of this study indicate that community participation, the competence of village assistants, the competence of village officials have a positive and significant effect on the successful management of village funds, and the quality of supervision of village councils and local government commitment have no effect on the successful management of village funds.